A co-simulation method for the analysis of train running performance on a sea-crossing bridge in crosswind environment. Issue 3 (February 2021) - Liu, Pin; Cui, Shengai; Guo, Chen; Cui, Enqi; Zhu, Bing
When a train crosses a bridge in a crosswind environment, the coupled vibration problem of the train-bridge system becomes prominent, and train safety and riding comfort are difficult to guarantee. Therefore, using the Pingtan Strait bridge in China as a case study, a co-simulation platform for the train-bridge system coupled vibration in crosswind environments was established based on computational fluid dynamics, finite element method, and the multi-body system dynamics. Based on this platform, dynamic response analysis of the train-bridge system was performed at different wind and train speeds. The results indicate that the dynamic response of the train and bridge under double-line conditions is greater than that under single-line conditions. With an increase in wind speed, the mid-span vertical displacement of the bridge changes little, while the lateral displacement increases significantly. Meanwhile, with increasing wind and train speeds, the train dynamic indexes obviously increase. Moreover, the dynamic index of the head car is the largest among all the train sections.